Brachycephalic Obstructive Airway Syndrome (BOAS) and Orofacial Cleft in a Dog:: Treatment with Palatoplasty, Staphyloplasty, and Unilateral Rhinoplasty - Wittzorecki Zaikowski, Andrielly; Lopes Zibetti, Francesca; Waller, Stefanie Bressan; Silva Vives, Patrícia; Duarte Pereira, Mariana; Goulart Teixeira, Alessandra; Brum Cleff, Marlete; Correia Costa, Paula Priscila (Acta Scientiae Veterinariae, 2025)
Background: Cleft lip and palate can be categorized as congenital craniofacial malformations, characterized by the failure of maxillary and palatal processes to fuse during the intrauterine period. This defect results in an opening in the palate, potentially causing communication between the nasal and oral cavities. Cleft lip and palate can present with varying degrees of severity. The treatment of choice for cleft lip and palate is surgical intervention, aimed at closing the defect to prevent oronasal communication. The following case report describes an American Bully dog with congenital malformations of cleft lip and palate and Brachycephalic Obstructive Airway Syndrome (BOAS). Case: A 1-year-and-3-month-old American Bully dog was diagnosed with BOAS, along with a unilateral cleft lip and palate. During the clinical examination, the dog showed characteristic symptoms of BOAS, including coughing, snoring, and exercise intolerance. The assessment also revealed moderate stenosis of the right nostril and food debris accumulation in the palatal cleft, which could lead to infections. Based on the diagnosis, three consecutive surgeries were performed: palatoplasty to correct the palatal cleft, unilateral rhinoplasty to treat the nasal stenosis, and staphylectomy to address the excessively long soft palate associated with BOAS. The palatoplasty involved an incision and coaptation of the cleft edges, while the staphylectomy resected the excess soft palate tissue. The rhinoplasty involved removing a fragment of tissue from the right nasal meatus through a wedge-shaped incision. The surgery was successful, and the patient showed improvement in respiratory symptoms during the postoperative period, although the owner did not attend follow-up appointments. Postoperative management included pain and anti-inflammatory medications, as well as recommendations for soft food and the use of an Elizabethan collar to prevent injury to the surgical site. The successful procedure highlights the importance of surgical correction in brachycephalic dogs with BOAS, improving their quality of life by alleviating respiratory difficulties and the risks associated with palatal clefts. Discussion: This case underscores the critical role of surgical intervention in managing congenital malformations in brachycephalic dogs. The patient underwent palatoplasty to correct a pre-existing palatal cleft, unilateral rhinoplasty of the right nostril due to moderate stenosis, and staphylectomy following a prior diagnosis of Brachycephalic Obstructive Airway Syndrome (BOAS). These procedures were essential for improving the animal's respiratory function and reducing the risks associated with the cleft palate, such as aspiration and bacterial infections. The rhinoplasty and staphylectomy successfully addressed the anatomical deformities caused by BOAS, alleviating respiratory symptoms and improving airflow. The palatoplasty, while primarily aimed at preventing complications from the cleft, also played a significant role in enhancing the patient's overall health by mitigating the risks of infections due to food debris accumulation in the cleft. While the cleft lip itself did not severely impact the animal's quality of life, it was important to consider the full spectrum of congenital malformations in this breed, as coexisting clefts are often present. Timely and comprehensive surgical intervention, as demonstrated in this case, is essential for improving the quality of life in brachycephalic dogs with congenital anomalies. This approach not only addresses immediate health concerns but also contributes to long-term well-being by enhancing both respiratory function and reducing the risk of secondary complications. Keywords: brachycephalic dog, cleft lip and palate, congenital defect, corrective surgery, craniofacial malformations, nasal stenosis.